Piperazines as nootropic agents: New derivatives of the potent cognition-enhancer DM235 carrying hydrophilic substituents. Issue 6 (15th March 2017) - Martino, Maria Vittoria; Guandalini, Luca; Di Cesare Mannelli, Lorenzo; Menicatti, Marta; Bartolucci, Gianluca; Dei, Silvia; Manetti, Dina; Teodori, Elisabetta; Ghelardini, Carla; Romanelli, Maria Novella
Graphical abstract: Abstract: The piperazine ring of the potent nootropic drug DM235 has been decorated with H-bond donor and acceptor groups (CH2 OH, CH2 OMe, CH2 OCOMe, COOEt); the aim was to insert new functional groups, suitable for further chemical manipulation. The influence of these modifications on nootropic activity was assessed by means of the mouse passive avoidance test; some of the newly synthesized molecules (alcohol7b, acetate8b and ester10d ) showed interesting in vivo potency. This makes it possible to use these functional groups for adding other residues, in order to increase molecular diversity, or for anchoring a biotin group, to obtain compounds useful to capture the biological target. Moreover, the new compounds will improve our knowledge of structure activity relationships of this family of drugs.